Strategi Penurunan Rasio Efisiensi Bank Syariah - Muhammad Taqwa Audiansyah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to find strategies that can be a solution for Islamic banks in reducing efficiency ratios. This is motivated by the high level of efficiency ratios in the Islamic banking industry which results in a low level of profitability. This situation ultimately made it difficult for Islamic banks to expand their businesses so that the growth of the Islamic banking industry slowed. The research method used is a qualitative approach, namely by conducting a literature review and accompanied by comparative analysis in other countries. The research resulted in the finding that the concept of platform sharing can be a strategy of Islamic banks to be a solution to reduce efficiency ratio. Platform sharing is a mechanism to use infrastructure owned by other entities but is still within the scope of the same business group. With this concept, it is hoped that the operational mechanism of Islamic banks can increase but can still reduce costs.